Measuring and Explaining Subjective Well-being in Korea - Shun Wang (Korea Development Institute (KDI), 2014)
Subjective well-being has attracted sharply increasing attention among researchers and policy makers in recent years. The public also pays a lot of attention to it, evidenced by the heavy use of the word "happiness" in media. Some researchers argue that subjective well-being measures should serve as important and reliable measures of human well-being, complementary to the more traditional, more material wellbeing measures such as Gross National Income (GNI). The World Happiness Report 2012 and 2013 strongly support the idea. The Organization for Economic Co-operation and Development (OECD) published Guidelines on Measuring Subjective Well-being in 2013 to help governments planning to measure subjective well-being, and to provide standards for how it is done. The Korean government seems to move in this direction: One of the main agenda of the government of Korea is to increase the happiness of each citizen. However, there is no comprehensive study on Korea's subjective well-being to guide policy makers. For example, Korea is often labeled as an unhappy society, as reported by media and perceived by the public, based on some scattered evidence. Is it true? Existing studies do not provide a clear answer. This study is the first comprehensive investigation into subjective well-being in Korea. We aim to show a clearer and more complete picture of Korea's subjective well-being, including its past and current status, its distribution over time, cohorts, and regions, and its determinants, based on the vast majority of available data. We then offer a few tentative policy suggestions.
Keywords: 330